Implementasi Hukum Ekonomi Syari’ah dalam Multi Akad di Perbankan Syari’ah - Haris Maiza Putra; Diana Farid; Moch. Asep Rusmana (IAIN Langsa, 2022)
This study discusses the application of Islamic economic law in the practice of multiple contracts in Islamic banks. The multi-contract is a contract between two parties to carry out muamalah transactions or transactions consisting of two or more contracts, for example, contracts consisting of buying and selling and ijarah contracts, buying and selling contracts, and so on. That all legal consequences of a combination contract, as well as all rights and obligations arising from it, are considered as an inseparable unit, having the same position as the legal consequences of the contract. This research is library research with a descriptive method. The results of the study conclude that multi-contract is a method of building Islamic economic law in a highly developed economic field. This goes beyond the limits of classical custom which is simply divided into 'aqd al-musamma and 'aqd ghair al-musamma. This division has been going on for a very long time and is only written in fiqh books without any theoretical and practical developments. The emergence of multi-contracts has transcended two aspects of legal norms, developed as a theory of contracts, and provided opportunities for Islamic banking to be easier and more open in developing products based on contracts that are avoided and free from usury activities. Keywords: Hybrid Contract; Law of Islamic Economic; Sharia Bank